Targeted Fe-doped silica nanoparticles as a novel ultrasound–magnetic resonance dual-mode imaging contrast agent for HER2-positive breast cancer - Li X (Dove Medical Press, 2019)
Xiaoyu Li,* Shujun Xia,* Wei Zhou, Ri Ji, Weiwei Zhan Ultrasound Department, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, China *These authors contributed equally to this work Background: Multimodal contrast agents with low toxicity and targeted modification have opened up new possibilities for specific imaging of breast cancer and shown broad application prospects in biomedicine and great potential for clinical transformation. In this work, a potential multifunctional imaging agent was developed by doping Fe into hollow silica nanoparticles (HS-Fe NPs), followed by modification with specific anti-HER2 antibodies, enabling the NPs to have dual-mode ultrasound (US)–magnetic resonance (MR)-specific imaging capacity with low toxicity.Methods: Anti-HER2 antibodies were conjugated to silane–polyethylene glycol (PEG)–COOH-modified HS-Fe (HS-Fe-PEG) NPs to produce HER2-targeted HS-Fe-PEG (HS-Fe-PEG-HER2) NPs. The toxicity of HS-Fe-PEG-HER2 NPs on targeted cells in vitro and blood and organ tissue of mice in vivo was investigated. Distribution in vivo was also studied. Confocal laser-scanning microscopy and flow cytometry were used to evaluate the targeting ability of HS-Fe-PEG-HER2 NPs in vitro. US and MR instruments were used for imaging both in vivo and in vitro.Results: The obtained HS-Fe-PEG-HER2 NPs (average diameter 234.42±48.76 nm) exhibited good physical properties and biosafety. In solution, they showed obvious enhancement of the US signal and negative contrast in T2-weighted MR imaging. The binding rate of HS-Fe-PEG-HER2 NPs to targeted cells (SKBR3) was 78.97%±4.41% in vitro. US and MR imaging in vivo confirmed that the HS-Fe-PEG-HER2 NPs were delivered passively into the tumor region of SKBR3 and bound specifically to tumor cells. Target enhancement was better than untargeted and targeted competition groups.Conclusion: HS-Fe-PEG-HER2 NPs have potential as a low-cytotoxicity and dual-mode US–MR-specific imaging agent. Keywords: dual-mode, ultrasound imaging, magnetic resonance imaging, HER2, breast cancer